Evaluation of Atmospheric Features in Natural Disasters due Frontal Systems over Southern Brazil - Jean Souza dos Reis; Weber Andrade Gonçalves; Diego Oliveira de Souza; David Mendes (Atmosphere, 2022)
This study evaluated the atmospheric pattern precursors to the occurrence of natural disasters (ND) in the southern region of Brazil (SRB) due to the passage of frontal systems (FS). The results can be used as prognostics to assist in risk management with a set of preventive and mitigating actions in order to minimize the impact of natural disasters suffered by the population. The natural disasters data were provided by the Centro de monitoramento e alertas de desastres naturais (Cemaden). For atmospheric analysis we used ERA5 reanalysis data, and the precipitation dataset was estimated from Integrated Multi-satellitE Retrievals for GPM (IMERG) from the Global Precipitation Measurement (GPM) mission. The most affected regions are the coast of Santa Catarina and the central-eastern region of Rio Grande do Sul. The results indicate that FS associated with ND are different from the other FS that affect the SRB. The observations were: a pattern of increase and accumulation of available convective potential energy west of the SRB before the event, especially in spring; a considerable increase in specific humidity at low levels associated with runoff east of the Andes; and an anticyclonic circulation at high levels similar to the Bolivian High. Analysis of rainfall behavior indicates that it is highest in the two days preceding the disaster. The mean precipitation values identified, together with atmospheric behavior observed in this study, allow us to identify the potential occurrence of a disaster in the cities of SRB in the passage of a frontal system.